TRANSLATION TECHNIQUES USED IN THE ENGLISH SUBTITLE OF “ALI BABA BURLESQUE” - Moses Hirja Meliala; Syahron Lubis; Zanuddin Zainuddin (Universitas Negeri Medan, 2019)
The objective of this study was to elaborate how is the realization of translation techniques in a micro-unit of Ali Baba Burlesque subtitle. The research methodology used in the research is qualitative design. The data were micro-units (words, clauses, phrases and sentences).The data were collected through documentary technique. The data were analyzed by using interactive model namely data condensation, data display and drawing conclusion.The findings of this study revealed that the realization of translation techniques in the English Subtitle of Ali Baba Burlesque consist of 2 groups consists of double techniques and triple techniques. For the double techniques namely Modulation and Reduction (0.2%), Modulation and Borrowing (4.3%), Literal and Borrowing (1.1%), Reduction and Borrowing (1.2%), Amplification and Borrowing (0.1%), Amplification and Generalization (0.1%) ,Establish Equivalence and Borrowing (0.1%). And triple techniques namely Amplification, Reduction and Modulation (0.1%). The conclusion: multiple techniques in Ali Baba Burlesque consist of triple techniques and double techniques. Double techniques that found in the micro-unit, mainly focused on Modulation but also associated with Borrowing. Meanwhile for triple techniques, it also focused on modulation but different from double technique, it associated with other techniques namely Amplification, and Reduction.Keywords:Translation,double, triple, multi techniques.,